The Relevance of a Good Internal Control System in a Computerised Accounting Information System - Lutui, R; Ahokovi, T (Security Research Institute, Edith Cowan University, 2018)
Advancements in information technology (IT) have enabled companies to use computers to carry out their activities that were previously performed manually. Accounting systems that were previously performed manually can now be performed with the help of computers. With all the advantages of computerized accounting software, business owners need to realize that problems do arise for a variety of reasons. Dependence on computers sometimes leads to bigger problems. This paper, therefore provide a detail information about the concept of internal control to its relevance in a computerised accounting information. This study also considers the trend between manual and computerised accounting system. This study concludes with recommendations on how to maximise the effectiveness of developing internal control systems of the computerized accounting systems which are characterized of providing appropriate safety to the systems. The systems can provide information characterized by reliability for the sake of taking decisions. These systems should integrated with other administrative and organizational systems.